(untitled) (London Journal of Research In Science: Natural and Formal, 2023)
In this brief paper, we show the calculations that confirm that Astrotheology is the correct and most advanced and ancient physics theory ever assembled.
Keywords: Oganessian; Benzene; AT Math.; Polarization; Light; Chiral molecules; Methanol; Electron Spin; Quantum Mechanics.; Periodic Table; Astrotheology.